Scattering Theory for 0-Perturbed PT -Symmetric Operators - Hrod, A. I.; Kuzhel', S. A. (Ukrains’kyi Matematychnyi Zhurnal, 2013)
The aim of the present work is to develop the scattering theory for 0-perturbed PT -symmetric operators by using the Lax–Phillips method. The presence of a stable C -symmetry leading to the property of selfadjointness (with proper choice of the inner product) for these PTPT -symmetric operators is described in terms of the corresponding C -matrix (scattering matrix).